Utilization of the Jump Rope Game as an Interactive and Fun PJOK Learning Media in Elementary Schools - Dhaifa Shafya Khasyia; Naila Azzahra; Nok Nessa Raudatul Zanah; Sekarningrum Nurhidayah; Agus Mulyana (COMPETITIVE: Journal of Education, 2025)
This study aims to obtain information to apply interactive and fun PJOK learning with traditional games, namely jumping rope. The research method used is a literature review. The results of this study show that PJOK is an important subject at the elementary school level that aims to develop motor skills, physical fitness, mental and social health of students. Interactive and fun PJOK learning is a learning approach that aims to make students more actively involved in the learning process. The jumping rope game is one of the simple but effective physical activities if used in PJOK learning at the elementary school level. Through jumping rope games, students can engage in fun physical activity and increase learning motivation. Playing jump rope helps improve muscle strength, coordination, balance, and agility.